Fortalecimiento de las políticas de salud pública contra el cáncer infantil: logros de Perú en el marco de la Iniciativa Mundial de la OMS contra el Cáncer Infantil - Maradiegue, E (2023)
Objective. To report the progress in Peru, since June 2019, in the implementation of the World Health Organization Global Initiative for Childhood Cancer using the CureAll framework, which can be replicated in low- and middle-income countries. Methods. A mixed method was used of participatory and documentary evaluation. The participatory evaluation included stakeholders from various government institutions, nonprofit organizations, and international partners. The documentary aspect consisted of a review of data on the regulatory environment, national projects, and interventions implemented. The Ministry of Health engaged more than 150 participants to form working committees, which have developed policy and regulatory documents to strengthen care services. Results. Achievements include a decrease in the national treatment abandonment rate from 18.6% to 8.5%, the approval of the Childhood Cancer Law, improvements in the management of patients with febrile neutropenia, and a reduction in rates of events of clinical deterioration and mortality of hospitalized patients. The Cure All implementation framework allows local teams to implement specific strategies and monitor early outcomes in pediatric oncology. Conclusions. The results obtained reflect the teamwork, the leadership of the authorities, the technical support of professionals, and the support of involved organizations. Further actions will be needed to guarantee sustainability, and monitoring tools are needed to assure success in the planned activities.